Age Moderates the Association of Aerobic Exercise with Initial Learning of an Online Task Requiring Cognitive Control. (19th November 2015) - O'Connor, Patrick J.; Tomporowski, Phillip D.; Dishman, Rodney K.
Abstract: The aim of this study was to examine whether people differed in change in performance across the first five blocks of an online flanker task and whether those trajectories of change were associated with self-reported aerobic or resistance exercise frequency according to age. A total of 8752 men and women aged 13–89 completed a lifestyle survey and five 45-s games (each game was a block of 46 trials) of an online flanker task. Accuracy of the congruent and incongruent flanker stimuli was analyzed using latent class and growth curve modeling adjusting for time between blocks, whether the blocks occurred on the same or different days, education, smoking, sleep, caffeinated coffee and tea use, and Lumosity training status ("free play" or part of a "daily brain workout"). Aerobic and resistance exercise were unrelated to first block accuracies. For the more cognitively demanding incongruent flanker stimuli, aerobic activity was positively related to the linear increase in accuracy [B=0.577%, 95% confidence interval (CI), 0.112 to 1.25 per day above the weekly mean of 2.8 days] and inversely related to the quadratic deceleration of accuracy gains (B=−0.619% CI, −1.117 to −0.121 per day). An interaction of aerobic activity with age indicated that active participants younger than age 45 had a larger linear increase and a smaller quadratic deceleration compared to other participants. Age moderates the association between self-reported aerobic, but not self-reported resistance, exercise and changes in cognitive control that occur with practice during incongruent presentations across five blocks of a 45-s online, flanker task. ( JINS, 2015, 21, 802–815)